Framingham Risk Score Assessment in Subjects with Pre-diabetes and Diabetes: A Cross-Sectional Study in Korea - Kwon, Hyuk Sang; Song, Kee Ho; Yu, Jae Myung; Kim, Dong Sun; Shon, Ho Sang; Ahn, Kyu Jeung; Choi, Sung Hee; Ko, Seung Hyun; Kim, Won; Lee, Kyoung Hwa; Nam-Goong, Il Seong; Park, Tae Sun (Journal of Obesity & Metabolic Syndrome, 2021)
This study aimed to evaluate cardiovascular risk in subjects with pre-diabetes and diabetes in Korea. In this pan-Korean, non-interventional, cross-sectional study, data were collected from medical records of 10 hospitals between November 2013 and June 2014. Subjects (aged ≥40 years) with medical records of dysglycemia and documentation of total cholesterol level, high-density lipoprotein cholesterol level, systolic blood pressure, and smoking status in the past 6 months were included. The primary endpoint was to determine the Framingham risk score (FRS). The relationships between FRS and cardiovascular risk factors, glycated hemoglobin, and insulin usage were determined by multiple linear regression analyses. Data from 1,537 subjects with pre-diabetes (n=1,025) and diabetes (n=512) were analyzed. The mean FRS (mean±standard deviation) in subjects with pre-diabetes/diabetes was 13.72±8.77. FRS was higher in subjects with diabetes than pre-diabetes ( <0.001). FRS in men with pre-diabetes was comparable to that in women with diabetes (13.80±7.37 vs. 13.35±7.13). FRS was elevated in subjects who consumed alcohol (2.66, =0.033) and with obesity-class II (6.10, =0.015) among subjects with diabetes (n=199), and was elevated in patients with left ventricular hypertrophy (11.10, =0.005), those who consumed alcohol (3.06, =0.000), were pre-obese (3.21, =0.002), or were obesity-class I (2.89, =0.002) among subjects with pre-diabetes (n=306) in comparison to subjects without these coexisting risk factors. Overall, Korean subjects with pre-diabetes and diabetes have an increased cardiovascular risk, which is significantly higher in those subjects with diabetes than with pre-diabetes. The present data can be used to develop measures to prevent and manage cardiovascular complications in Koreans with impaired glucose metabolism.